Cognitive Function Characteristics in Patients with Myasthenia Gravis - Khairina, Yunika; Fitri, Aida; Fitri, Fasihah Irfani (Journal of Society Medicine, 2023)
Introduction: Myasthenia gravis (MG) is one of the most common neuromuscular junction disorders with various clinical presentations. Several studies showed cognitive function decline in MG patients which affects cognitive domains in memory, attention, executive function, and verbal. The involvement of the central cholinergic system, known as central cholinergic deficits are thought to manifests as impaired cognitive function in patients with MG. The purpose of this study was to evaluate cognitive function characteristic in patients with myasthenia gravis. Method: This study used a cross-sectional design, involved 33 myasthenia gravis patients in Neurology Outpatient Clinic of Haji Adam Malik Central General Hospital and 33 subjects in healthy control group. Cognitive function tests were performed using the Indonesia version of Montreal Cognitive Assessment (MoCA-Ina). Mann-whitney test was performed to evaluate cognitive performance difference in both groups. Results: : The results were compared between MG and healthy control group. The mean of MoCA-Ina score was significantly lower in MG group compared to healthy control group. The result of this study showed difference in cognitive performance between MG patients and healthy control group (p<0.001). This study showed delayed memory, attention, verbal, abstraction, visuospatial and executive function performance was decline in MG patients. Conclusion: This study concludes significant difference of cognitive performance based on MoCA-Ina scores between myasthenia gravis patients and healthy control group.